2011
DOI: 10.1371/journal.pone.0023142
|View full text |Cite
|
Sign up to set email alerts
|

Whole Transcriptome Profiling of Successful Immune Response to Vibrio Infections in the Oyster Crassostrea gigas by Digital Gene Expression Analysis

Abstract: The cultivated Pacific oyster Crassostrea gigas has suffered for decades large scale summer mortality phenomenon resulting from the interaction between the environment parameters, the oyster physiological and/or genetic status and the presence of pathogenic microorganisms including Vibrio species. To obtain a general picture of the molecular mechanisms implicated in C. gigas immune responsiveness to circumvent Vibrio infections, we have developed the first deep sequencing study of the transcriptome of hemocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
93
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 60 publications
0
93
1
Order By: Relevance
“…In addition, this study represents the first combination of iTRAQ and a labelfree proteomic analysis to enhance our understanding of a beneficial symbiosis. Proteomic and gene expression studies in other organisms, including oysters and pigs, have revealed that similar genes and proteins (cathepsins, GM2AP, heat shock protein 22, and cytoskeletal proteins) are altered by both pathogenic and beneficial bacterial colonization (70,71). Few studies have combined both iTRAQ and label-free proteomics; however, label-free methods have been shown to identify a greater number of significantly different proteins than labeling approaches, similar to what was observed in this study (72,73).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this study represents the first combination of iTRAQ and a labelfree proteomic analysis to enhance our understanding of a beneficial symbiosis. Proteomic and gene expression studies in other organisms, including oysters and pigs, have revealed that similar genes and proteins (cathepsins, GM2AP, heat shock protein 22, and cytoskeletal proteins) are altered by both pathogenic and beneficial bacterial colonization (70,71). Few studies have combined both iTRAQ and label-free proteomics; however, label-free methods have been shown to identify a greater number of significantly different proteins than labeling approaches, similar to what was observed in this study (72,73).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, 12 h and 24 h infections with Flavobacterium induced higher levels of immune lectin receptor 2 transcripts, above the control seawater-incubation expression experiments. In a recent transcriptome profiling study, using the Pacific Crassostrea gigas as a model to address immune responses to the virulent Vibrio splendidus and Vibrio aestuarianus bacteria, several immune genes were characterised in relation to the oyster capability to survive pathogenic Vibrio infections, including the Rhamnose-binding lectin, C-type lectin 2 and Metallothionein IV whose expression were up-regulated in surviving oysters (De Lorgeril et al, 2011). Xue et al (2010) also evidenced the involvement of a new lysozyme in the oyster Crassostrea virginica which also agrees with the finding that B. azoricus lysozyme is up-regulated in Flavobacterium infections.…”
Section: Discussionmentioning
confidence: 99%
“…Lysozyme expression has been detected and localized in digestive cells of digestive tubules, gills and mantle [56,58,60,61]. However, CGL-1 was shown to be differentially expressed in hemocytes following C. gigas infection with the pathogenic V. tasmaniensis LGP32 compared to a non-virulent one [62]. Besides, lysozyme activity has been shown to increase in hemolymph following a co-stimulation of LPS and an oyster recombinant tumor necrosis factor, rCg-TNF1 [63].…”
Section: Lysozymesmentioning
confidence: 99%